Translating the Islamic Education Philosophy into Actions; Muslim Universities Vice-Chancellors’/Presidents’ Forum. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2012)
Universiti Sains Malaysia, in collaboration with Higher Education Leadership Academy (AKEPT), organised the second Muslim Universities Vice-Chancellors’ Forum (MUVCF) with National Higher Education Research Institute (IPPTN) as the MUVCF Secretariat on 3–4 December 2012 at The Royale Chulan Kuala Lumpur.